Synthesis and characterization of new ruthenium complexes with active ligands against Chagas' disease - Otero, Lucía (2003)
Chagas' disease, considered incurable, is a major third world parasitosis that affects millions of people in Latin America. Previous work has shown that ruthenium clotrimazole complexes are more active against Trypanosoma cruzi, causative agent of Chagas' disease, than the corresponding free ligand. In this work, the synthesis and characterization of a series of new Ru(II) complexes with different antitrypanosomal active compounds is presented. Complexes of general formulae [RuIICl2(dmso)2L], where dmso=dimethylsulfoxide and L=5-nitro-2-furaldehyde semicarbazone (L1), N4-n-butyl-5-nitro-2-furaldehyde semicarbazone (L2) or 3-(5-nitrofuryl)acroleine semicarbazone (L3), were prepared in good yields by reaction of [RuIICl2(dmso)4] with L in ethanol or toluene solutions. Complexes were characterized by elemental analyses and electronic, FTIR, 1H and 13C NMR spectroscopies. Crystal and molecular structures of [RuCl2(dmso)2L1] and [RuCl2(dmso)2L2] were determined by X-ray diffraction methods. In both crystals the ruthenium metal atom is in a quite similar elongated octahedral environment, equatorially coordinated to the semicarbazone molecule, acting as a bidentate ligand through its azomethynic nitrogen and carbonylic oxygen atoms. The sixfold coordination is completed with the sulfur atoms of two dimethylsulfoxide ligands at cis positions and two chlorine ions at the axial positions. The proposed formula for L3 complex was supported by FTIR, NMR and theoretical studies. NOE-NMR experiments allowed to assign L3 spatial distribution in the complex. © 2002 Elsevier Science B.V. All rights reserved.